EGCG Protects against 6-OHDA-Induced Neurotoxicity in a Cell Culture Model - Dan Chen; Anumantha G. Kanthasamy; Manju B. Reddy (Parkinson's Disease)
Background. Parkinson’s disease (PD) is a progressive neurodegenerative disease that causes severe brain dopamine depletion. Disruption of iron metabolism may be involved in the PD progression. Objective. To test the protective effect of (−)-epigallocatechin-3-gallate (EGCG) against 6-hydroxydopamine- (6-OHDA-) induced neurotoxicity by regulating iron metabolism in N27 cells. Methods. Protection by EGCG in N27 cells was assessed by SYTOX green assay, MTT, and caspase-3 activity. Iron regulatory gene and protein expression were measured by RT-PCR and Western blotting. Intracellular iron uptake was measured using 55Fe. The EGCG protection was further tested in primary mesencephalic dopaminergic neurons by immunocytochemistry. Results. EGCG protected against 6-OHDA-induced cell toxicity. 6-OHDA treatment significantly (p<0.05) increased divalent metal transporter-1 (DMT1) and hepcidin and decreased ferroportin 1 (Fpn1) level, whereas pretreatment with EGCG counteracted the effects. The increased 55Fe (by 96%, p<0.01) cell uptake confirmed the iron burden by 6-OHDA and was reduced by EGCG by 27% (p<0.05), supporting the DMT1 results. Pretreatment with EGCG and 6-OHDA significantly increased (p<0.0001) TH+ cell count (~3-fold) and neurite length (~12-fold) compared to 6-OHDA alone in primary mesencephalic neurons. Conclusions. Pretreatment with EGCG protected against 6-OHDA-induced neurotoxicity by regulating genes and proteins involved in brain iron homeostasis, especially modulating hepcidin levels.